Quantitative Determination of thymoquinone in Nigella Sativa and its nano formulation using validated stability indicating HPTLC densiometric method - Taleuzzaman, Mohamad; Imam, Syed Sarim; Gilani, Sadaf Jamal (International Current Pharmaceutical Journal, 2018)
An accurate and stability indicating high-performance thin layer chromatographic method (HPTLC) was developed and validated for the quantification of thymoquinone (TQ) as per the ICH guidelines. The analysis was carried out on the aluminum plate using n-hexane: ethyl acetate: methanol (7:2:1 v/v/v) as the mobile phase and the densitometric determination was carried out by TLC scanner (CAMAG) at 254 nm. The developed method was validated for different parameters like linearity, precision, recovery, robustness, and stressed stability study. The developed analytical method was found to be linear in the concentration range of 75-500 ng band-1 with regression value closer to unity (r2 = 0.997). The developed system was found to give compact spots for thymoquinone (Rf 0.77) with the limit of detection and limit of quantification (18 and 54 ng band-1) respectively. Further, the study showed accuracy, precision and repeatability were all within the required limits. The stress degradation study of TQ showed well separated degraded peak from the pure thymoquinone. The mean recoveries measured at three concentrations were more than 95% with RSD ≤ 3%. The method has been successfully applied in the analysis and routine quality control of herbal material and formulations containing TQ. Taleuzzaman et al., International Current Pharmaceutical Journal, September 2017, 6(10): 53-60 http://www.icpjonline.com/documents/Vol6Issue10/01.pdf